Characteristic accumulation of PCDD/Fs in pine needles near an MSWI and emission levels of the MSWI in Pearl River Delta: A case study. (August 2017) - Chen, Pei; Xiao, Xiao; Mei, Jun; Cai, Ying; Tang, Yuhui; Peng, Ping'an
Abstract: Pine needle samples were collected near a municipal solid waste incinerator (MSWI) in Pearl River Delta, southern China, as well as the stack gas and dust samples of the MSWI were simultaneously collected. Polychlorinated dibenzo- p -dioxins and polychlorinated dibenzofurans (PCDD/Fs) were analyzed following the USEPA Method 1613B. The concentration of PCDD/Fs in the pine needles (137–625 ng/kg, 25–51 ng I-TEQ/kg) is the highest level ever detected in China. Congener profile comparison and principal component analysis (PCA) confirmed the MSWI as an important emission source of environmental PCDD/Fs. The PCDD/Fs in the pine needles mainly depended on the atmospheric concentration, exposure time and also the wind direction. The accumulation of PCDD/Fs in this species did not occur at a steady rate, and the total concentrations covered up the actual photolysis information. Gas-phase partitioning of compounds in the atmosphere was the dominant process through which PCDD/Fs were adsorbed onto the pine needle surface in contrast with particle-phase deposition, and subsequent environmental behavior varied between the congeners. Photo-degradation was the major transformation process as PCDD/Fs were adsorbed onto the pine needle surfaces. Higher chlorinated PCDD/Fs were more recalcitrant to photo-degradation than those that were less chlorinated, and PCDDs were more resistant to photo-degradation than PCDFs. On the other hand, the strong ability of lipid-rich pine needles to accumulate dioxin compounds indicates they can be used as the absorption sink of PCDD/Fs in heavily polluted areas because it is easier to dispose of pine needles than it is to clean contaminated air. Highlights: Extremely high levels of PCDD/Fs were found in pine needles near an MSWI. PCDD/Fs in pine needles mainly depend on atmospheric contents, exposure time and wind direction. PCDD/Fs adsorbed to pine needle are mainly via gas-phase partition from atmosphere. Emission sources impact dioxin distribution patterns in pine needles. Total PCDD/F levels of pine needles cover up the actual photolysis information.